(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Postpartum hemorrhage is the most common cause of morbidity and mortality. Recognition of PPH and management is based on achieving adequate uterine tone and maintaining maternal hemodynamic stability. Several drugs are available for the management of PPH. We in the current study tried to evaluate the efficacy of Tranexamic acid in reducing blood loss during normal labor. Methods: Based on the inclusion and exclusion criteria n=80 females were included in the current study. Administration of 10 IU injection Oxytocin I.V was given to mother as soon as the delivery of anterior shoulder of the baby followed by injection of Tranexamic acid 500 mg slow IV infusion for 5 minutes in the study group. 10 IU injection Oxytocin I.V was followed by placebo injection of normal saline 5 ml was given in control group. Results: The mean fall in hemoglobin level was 1.67 gm% in study group and 2.15 gm% in control group. The mean fall in hematocrit was 1.92% in study group and 4.04% in control group. The post-delivery hemoglobin and hematocrit were significantly reduced in the control group compared to the study group. The number of cases in study group that required blood transfusion was n=2(5%) and number of cases in the control group requiring the blood transfusion was n=6(15%). Conclusion: Within the limitations of the current study, it can be concluded that the among the women with vaginal delivery who received prophylactic oxytocin and tranexamic acid reduced the blood loss from the time of delivery to 2-hour post-partum. The need for additional uterotonics and maternal blood transfusion is significantly reduced in the study group compared to the control group.